2007
DOI: 10.2140/gtm.2007.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration of Heegaard genus, a survey

Abstract: We survey known (and unknown) results about the behavior of Heegaard genus of 3-manifolds constructed via various gluings. The constructions we consider are (1) gluing together two 3-manifolds with incompressible boundary, (2) gluing together the boundary components of surface times I, and (3) gluing a handlebody to the boundary of a 3-manifold. We detail those cases in which it is known when the Heegaard genus is less than what is expected after gluing.Comment: This is the version published by Geometry & Topo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…See eg Bachman and Derby-Talbot [3] or Lackenby [15] for descriptions of the construction in simpler cases.…”
Section: Stabilizationmentioning
confidence: 99%
“…See eg Bachman and Derby-Talbot [3] or Lackenby [15] for descriptions of the construction in simpler cases.…”
Section: Stabilizationmentioning
confidence: 99%
“…There exist examples which show that an amalgamation of two minimal genus Heegaard splittings of M 1 and M 2 is stabilized, see [1], [8] and [19] etc. On the other hand, it has been shown that under some conditions on the manifolds, the gluing maps, or the distances of the factor manifolds, the equality g(M ) = g(M 1 ) + g(M 2 ) − g(F ) holds, see [9], [10], [20], [7] and [21] etc.…”
Section: Introductionmentioning
confidence: 99%
“…There exist examples which show that an amalgamation of two minimal genus Heegaard splittings of M 1 and M 2 could be stabilized (refer to [1,5,13] etc. ), in that case g(M ) < g(M 1 ) + g(M 2 ) − g(F ) does occur.…”
Section: Introductionmentioning
confidence: 99%